William S. answered • 01/20/14

Experienced scientist, mathematician and instructor - William

4x - 3(x - 2y) + (1/2)(6x - 8y) =

4x - 3x + 6y + 3x - 4y =

4x + y(6 - 4) = 4x + 2y =

**2(2x + y)**Jessica M.

asked • 01/20/14Express the answer from the equation 4x-3 (x-2y)+1/2 (6x-8y) as an equivalent expression in factored form.

Follow
•
3

Add comment

More

Report

William S. answered • 01/20/14

Experienced scientist, mathematician and instructor - William

4x - 3(x - 2y) + (1/2)(6x - 8y) =

4x - 3x + 6y + 3x - 4y =

4x + y(6 - 4) = 4x + 2y = **2(2x + y)**

Vivian L. answered • 01/20/14

Microsoft Word/Excel/Outlook, essay composition, math; I LOVE TO TEACH

Hi Jessica;

4x-3 (x-2y)+1/2 (6x-8y)

Let's distribute...

4x-3x+6y+3x-4y

Let's combine like terms...

4x+2y

2(2x+y)

Ask a question for free

Get a free answer to a quick problem.

Most questions answered within 4 hours.

Find an Online Tutor Now

Choose an expert and meet online. No packages or subscriptions, pay only for the time you need.